Antecedents of Organizational Commitment: The Mediating Effect of Job Satisfaction in Saudi Labor Sector - Nassani, Abdelmohsen; Alhur, Buthinah; Aljorais, Norah (The Arab Journal of Administration, 2022)
In the Saudi labor sector, this study aims to determine the function of job satisfaction as a mediator in the relationship between authentic leadership and organizational commitment, as well as mindfulness and organizational commitment. The respondents of this research were 204 Saudi employees. The information was gathered using electronic questionnaires and examined in three stages: descriptive statistics, confirmatory factor analysis to test dimensionality, and path analysis. The descriptive statistics and correlation matrices of all variables were analyzed in the first phase. The confirmatory factor analysis and reliability consistencies were used in the second phase to look into the unit-dimensionality of each variable. Amos was used to do the path analysis in the third phase. The findings of the study revealed that there is a link between mindfulness and job satisfaction, there is also link and relationship between authentic leadership and job satisfaction. As well as a significant relationship between job satisfaction and organizational commitment and between mindfulness and organizational commitment. The findings of this study can be used as a guide for organizations in the Saudi sector to improve employee satisfaction and, as a result, support corporate goals